PLANO DE RETROFIT DE ENVOLTÓRIA DE EDIFICAÇÃO CORPORATIVA COM ANÁLISE DE CUSTO-BENEFÍCIO EM EFICIÊNCIA ENERGÉTICA - ERICK FRAIHA MACHADO (2023)
Whereas the international effort to reduce environmental impacts, CO2 emissions and energy consumption, this work focus in the use of construction elements with improved energy performance in order to contribute to the sustainability and energy efficiency in the built environment. The objective of this dissertation is to present a envelop retrofit plan with payback and energy performance analysis of three different retrofit intervention proposals (MBI, MMI and MAI) in a corporate public building of the Empresa Brasileira de Correios e Telégrafos, located in a tropical savanna climate. Through parametric computer simulation, the energy performance, thermal and light performance of the intervention proposals defined from the initial investment cost were analyzed. The modeling was done in Rhinoceros®. Simulation settings were performed on the Grasshopper® platform with Honeybee and Ladybug® plug-ins. These were performed using Honeybee, Ladybug®, EnergyPlusTM, OpenStudio® and Radiance. The results showed better comfort conditions in the use of natural ventilation in the MMI with 20.6% of the occupancy time with a thermal sensation of comfort. Better luminous performance was verified in the MAI considering Daylight Autonomy of 42.9% of the occupation time and 54.4% of useful illuminance between 300 Lux and 1000 Lux. The cost-benefit analysis by payback calculation did not present a satisfactory result for any retrofit proposal, but the MAI proved to be the most viable when considering a 62.57% reduction in energy consumption for cooling.